Ultrasonography-based prediction of carotid artery atherosclerosis using multiple abdominal fat indices - Jain Mohit; Panda Subhasish; Chandak Shruti; Malhotra Ankur; Dash Subhashree; Afifa Umme (Journal of Ultrasonography)
Abdominal obesity is recognized as the best predictor of cardiovascular disease risk. While body mass index has traditionally been used to measure obesity, recent evidence suggests that visceral adipose tissue may be a better indicator of cardiovascular disease risk. Various surrogate imaging markers of visceral adipose tissue have recently been described, such as posterior right perinephric fat thickness, preperitoneal fat thickness, and the abdominal wall fat index. This study aimed to examine the link between atherosclerosis through measurement of carotid intima-media thickness and markers of abdominal obesity using ultrasonography.